A Preliminary Report of the Survey on Teaching Strategies, Phase 1 An Evaluation by Students in the B. S. Psychology Program - Maranda, Alma G.; Castro, Luz C. Sevidal; Arquisal, Amabelle B. (2010)
Several methods and techniques of instruction had been employed by the CASS Faculty over the past years. The effectiveness of these techniques has to be assessed, an undertaking which takes into account the students' evaluation of these techniques. Toward this end, a study (Phase 1) had been conducted in order to elicit the students' evaluation of teaching methods employed in the foundation courses taken at the College of Arts and Social Sciences and in the major courses in their respective degree programs. Phase 1 of the study was designed as a survey among seniors/ graduating students (as of first semester and second semester of School Year 2006-2007) simultaneously in six (6) degree programs of the CASS. This report focuses on the survey undertaken among respondents in the degree program, Bachelor of Science in Psychology.

The objectives of this report are: to describe the BS Psychology students' evaluation of the effectiveness of techniques employed in foundation courses at the CASS (English, Filipino, Anthropology, History, Humanities, Philosophy, Political Science, and Sociology); to describe their evaluation of the effectiveness of techniques employed in their major courses; to determine the techniques preferred most by the students.

The results of this study are significant for several reasons. The findings serve as one basis for analyzing the effectiveness of classroom strategies and for encouraging students to achieve optimum learning. Second, teachers can enhance the students' potentials to the fullest. Teachers will be encouraged to ensure that their methods of teaching are effective, thereby generating positive response of students to their subjects. Lastly, the findings can be a strong basis for designing programs responsive to the need to enrich and strengthen classroom instruction strategies.
Keywords: Psychology education; Curriculum evaluation